2022
DOI: 10.3389/fpls.2022.837200
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a Hyperspectral Imaging System Used to Estimate Wheat Grain Protein: A Review

Abstract: Recent research advances in wheat have focused not only on increasing grain yields, but also on establishing higher grain quality. Wheat quality is primarily determined by the grain protein content (GPC) and composition, and both of these are affected by nitrogen (N) levels in the plant as it develops during the growing season. Hyperspectral remote sensing is gradually becoming recognized as an economical alternative to traditional destructive field sampling methods and laboratory testing as a means of determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…It was shown that when using several popular classical ML methods, including Multi Layer Perceptron (MLP), the accuracy of plant drought state detection based on the full spectral characteristic of plants HSI, as well as its derivative, turned out to be higher than the accuracy obtained on a combination of 9 vegetation indices. Review [14] over the past almost 25 years is devoted to the development, based on ML and HSI data, of algorithms for detecting the quality of wheat grain protein and its relationship with nitrogen status.…”
Section: Hsi and Ai In Agriculturementioning
confidence: 99%
“…It was shown that when using several popular classical ML methods, including Multi Layer Perceptron (MLP), the accuracy of plant drought state detection based on the full spectral characteristic of plants HSI, as well as its derivative, turned out to be higher than the accuracy obtained on a combination of 9 vegetation indices. Review [14] over the past almost 25 years is devoted to the development, based on ML and HSI data, of algorithms for detecting the quality of wheat grain protein and its relationship with nitrogen status.…”
Section: Hsi and Ai In Agriculturementioning
confidence: 99%
“…Recently, significant progress has been made in the field of reflectance spectral analysis of different vegetation indices (VIs), including normalised difference vegetation index (NDVI) (Hansen & Schjoerring, 2003 ), medium terrestrial chlorophyll index (MTCI) and normalised pigments chlorophyll ratio index (NPCRI) (Tan et al, 2018 ), normalised water index (NWI) (Babar et al, 2006 ) and structural insensitive pigment index (SIPI) (Robles‐Zazueta et al, 2021 ) which are derived from the canopy with respect to plant nitrogen content. HSI application using different VIs to estimate plant nitrogen content has been reviewed elsewhere (Ma et al, 2022 ).…”
Section: Hsi —An Innovative Technology For Studying Grain Qu...mentioning
confidence: 99%
“…Recent reviews have focused on the use of HSI to investigate quality characteristics in cereals, including wheat (Caporaso et al, 2018b ), wheat grain protein estimation (Ma et al, 2022 ), quality assessment at different stages of supply chain (Karmakar et al, 2022 ), application of HSI in plant phenotyping (Sarić et al, 2022 ) and comparison of HSI with near infrared spectroscopy to investigate quality characteristics (Tahmasbian et al, 2021 ). In contrast, we will discuss in this review how the loss of genetic diversity in modern wheat breeding could have led to selection against grain quality and key traits that influence the nutritional value of wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, HRS technology, with its contactless observation, high spectral resolution, and flexibility, is gradually becoming recognized as a suitable alternative to traditional field sampling methods to obtain crop information ( Park and Lu, 2015 ; Ma et al., 2022 ). In the field of agricultural, the most important ability of HRS is that it can obtain sufficient hyperspectral reflectance data of crops with a non-destructive mean, and with the assistance of various regression modeling algorithms, the relationship between reflectance data and various crop agronomic traits (e.g., leaf nitrogen, chlorophyll, water content, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Thus, references cited in this review were mainly published from 2010 to 2022. Furthermore, according to our retrieval results, the existing reviews related HRS and agriculture applications cover various aspects: UAV-borne HRS ( Xiang et al., 2019 ), hyperspectral imaging technologies ( Adão et al., 2017 ; Mahlein et al., 2018 ), precision agricultural applications ( Bégué et al., 2018 ; Latif, 2018 ), leaf area index (LAI) ( Ke et al., 2016 ), crop yield prediction and nitrogen status assessment ( Chlingaryan et al., 2018 ; Fu et al., 2021 ), wheat grain protein ( Ma et al., 2022 ), etc. The rest of this article is organized as follows: in section 2, we introduce the principles and workflow of HRS applications for PTA; in section 3, we compare three commonly used hyperspectral data acquisition system platforms; the details of specific applications and methodologies are presented in section 4; the discussion of issues and recommendations is arranged in section 5; the conclusion is in section 6.…”
Section: Introductionmentioning
confidence: 99%